Gestational jet lag predisposes to later-life skeletal and cardiac disease. (4th May 2019) - Chaves, Inês; van der Eerden, Bram; Boers, Ruben; Boers, Joachim; Streng, Astrid A.; Ridwan, Yanto; Schreuders-Koedam, Marijke; Vermeulen, Marijn; van der Pluijm, Ingrid; Essers, Jeroen; Gribnau, Joost; Reiss, Irwin K. M.; et al.
ABSTRACT: Circadian rhythm disturbance (CRD) increases the risk of disease, e.g. metabolic syndrome, cardiovascular disease, and cancer. In the present study, we investigated later life adverse health effects triggered by repeated jet lag during gestation. Pregnant mice were subjected to a regular light-dark cycle (CTRL) or to a repeated delay (DEL) or advance (ADV) jet lag protocol. Both DEL and ADV offspring showed reduced weight gain. ADV offspring had an increased circadian period, and an altered response to a jet lag was observed in both DEL and ADV offspring. Analysis of the bones of adult male ADV offspring revealed reduced cortical bone mass and strength. Strikingly, analysis of the heart identified structural abnormalities and impaired heart function. Finally, DNA methylation analysis revealed hypermethylation of miR17-92 cluster and differential methylation within circadian clock genes, which correlated with altered gene expression. We show that developmental CRD affects the circadian system and predisposes to non-communicable disease in adult life.